LAW ENFORCEMENT EFFORTS AGAINST IMMIGRATION CRIMES - Nilam Rizky Anugerah; Surya Pranata (Journal of Law and Border Protection, 2019)
the development of information technology, communication and transportation are tendency in terms of increasing relations between nations globally which drives human traffic between countries, giving rise to the complexity of the problems of human mobility between countries. Based on selective policy that upholds the value of human rights, regulated entry of foreigners into the territory of Indonesia, so also for foreigners who obtain a residence permit in the territory of Indonesia must be in accordance with the intent and purpose of being in Indonesia. Immigration crime is basically in addition to its nature as an international and transnational crime and is carried out individually or in an organized manner, it is also very detrimental and endangering to the community so that a severe criminal threat is needed in order to provide a deterrent effect for foreigners who commit violations. forms of supervision of foreigners, namely, supervision of foreigners, field supervision, immigration detention centers, and prevention and deterrence.